Transition metal fluoride cathodes in liquid lithium metal batteries - Olbrich, LF (2024)
The aviation industry is responsible for more than 2% of the world’s energy related carbon dioxide emissions. Although it is among the fastest-growing sources of emissions, it is also one of the most challenging sectors to decarbonize. Electrifying aviation to reduce emissions necessitates the development of next generation batteries that offer higher energy densities and enhanced safety. In addition, rate capabilities that are compatible with the power requirements during take-off and landing are necessary. Intercalation cathodes are intrinsically limited in energy density and pose an inherent safety risk due to the risk of oxygen release at high temperatures, which can lead to a thermal runaway. In contrast, transition-metal-fluoride (TMF) cathodes offer a three- to five-fold increase in charge capacity due to a multi-electron conversion mechanism and excellent thermal stability due to the ionic nature of the metal-fluoride bond. When paired with a Li-metal anode, stack-level energy densities of over 700Wh kg−1 can be achieved. Their practical implementation, however, faces challenges due to their low electronic and ionic conductivity and low cycling reversibility. This thesis lays the foundational groundwork for the practical implementation of a TMF-Li-metal battery by comprehensively examining its cathode, electrolyte, and anode. First, a new FeF2 wet-milling strategy and composite preparation technique are developed, which enable unprecedented cycling reversibility for composites with high active material contents. The cathodes are used to examine the effect of bis(fluorosulfonyl)imide anions and temperature on electrochemical behavior. The results indicate the viability of TMF cathodes to meet technical requirements for electric flight, however, they highlight the importance of electrolyte optimization. Second, an electrolyte development tool based on operando Raman gradient analysis is presented. Utilizing an external reference enables the visualization of concentration gradients of every Raman active species in the electrolyte. Gradients can be used to extract transport and thermodynamic properties of the electrolyte in a unified setup, which are key parameters to determine a battery’s rate capability. The external reference further enables the detection of Li-filament propagation. By incorporating a thermal chamber, the effect of temperature on transport and solvation in electrolytes can be studied. Third, the electrolyte-Li metal interphase, a crucial determinant for cycling reversibility, is studied using electrochemical impedance spectroscopy. The effect of cell design, Li preparation, temperature, salt concentration, and Li activity on the cell impedance is explored. The results are used to deconvolute interphase impedances from the native passivation layer and solid electrolyte interphase.